2021
DOI: 10.22541/au.161827907.73465337/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Endotypes of Chronic Rhinosinusitis; relationships to disease phenotypes, pathogenesis, clinical findings and treatment approaches.

Abstract: Chronic rhinosinusitis (CRS) is a common clinical syndrome that produces significant morbidity and costs to our health system. The study of CRS has progressed from an era focused on phenotype to include endotype based information. Phenotypic classification has identified clinical heterogeneity in CRS based on endoscopically observed features such as presence of nasal polyps, presence of comorbid or systemic diseases and timing of disease onset. More recently, laboratory-based findings have established CRS endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 161 publications
(228 reference statements)
0
35
0
Order By: Relevance
“…ECRS is a persistent sinonasal inflammatory condition attributed to dominant eosinophilia driven by Th2 cytokines (e.g., IL‐4, IL‐5, IL‐13) 49 . Due to its frequent association with refractory disease and NP recurrence following therapeutic intervention, 50,51 eosinophilia is an important target in CRS patients 3,9 . In general, ECRS is first treated with corticosteroids in an oral or topical route, which is frequently inefficacious and related to adverse systemic effects 52–54 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ECRS is a persistent sinonasal inflammatory condition attributed to dominant eosinophilia driven by Th2 cytokines (e.g., IL‐4, IL‐5, IL‐13) 49 . Due to its frequent association with refractory disease and NP recurrence following therapeutic intervention, 50,51 eosinophilia is an important target in CRS patients 3,9 . In general, ECRS is first treated with corticosteroids in an oral or topical route, which is frequently inefficacious and related to adverse systemic effects 52–54 .…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] A range of inflammatory mediators and effector cells orchestrate in a complex manner, leading to the development of CRS with varying inflammatory endotypes and clinical phenotypes. [3][4][5] Amongst the various inflammatory cells infiltrating the sinonasal mucosa of CRS patients, primary attention has been paid to the regulation of eosinophils due to their frequent association with refractory and recurrent CRS. 6,7 Accordingly, strategies that target eosinophil survival and migration in addition to topical or oral corticosteroids have been pursued as a promising treatment modality to resolve eosinophilic inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…1 This recommendation is based on numerous studies that illustrate that for most individuals the major division lies between type 2 and nonetype 2 responses. 47,48 The biomarkers of CRS inflammatory endotypes are directly ascertained from patients' biological tissues that can include blood, nasal mucus, and sinonasal mucosal tissue. The sinonasal mucosa is the gold standard tissue to sample because it is the site of the disease, although nasal mucus and blood biomarkers are correlated with varying degrees.…”
Section: Epidemiology Of Crs Endotypesmentioning
confidence: 99%
“…Chronic rhinosinusitis (CRS) is a chronic inflammatory disease of the upper respiratory tract which results in clinical syndromes, including nasal discharge, nasal obstruction, and reduction and loss of smell [1,2]. Previous epidemiologic studies showed that CRS is one of the most common disorders with an estimated prevalence of 2-4% according to the geographic region surveyed [3,4].…”
Section: Introductionmentioning
confidence: 99%